Performance evaluation of children's holiday camp of the Ryazan’ region - O V Kazaeva (RUDN Journal of Medicine, 2015)
The article evaluates the effectiveness of summer health campaign in the Ryazan region in accordance with methodical recommendations. The results indicate a positive influence of the summer country rest on the health of children and adolescents.